Internal security in local development policy - Hajduga, Piotr; Łuczyszyn, Andrzej (Bezpieczeństwo wewnętrzne w polityce rozwoju lokalnego, 2020)
In today’s social, economic, and political reality, security environment needs to have appropriate conditions for its functioning. Stabilising these conditions is becoming indispensable due to the ongoing changes in people’s economic activity manifested by new forms of management and based on new technologies. Internal security is determined by various factors and is of interest to different parties. Currently, as local communities are gaining vital importance, a large part of development initiatives is transferred to the local level. The links between internal and social security as well as local development policy, social policy, and welfare policy are becoming increasingly visible
Biblioteka Regionalisty, 2020, Nr 20, s. 49-58
Keywords: internal security; local development policy; social policy; local economic policy; bezpieczeństwo wewnętrzne; polityka rozwoju lokalnego; polityka społeczna; lokalna polityka gospodarcza